Enhancing Halal Product Exports: Indonesia's Halal And K Pop Collaboration - Pramono, Adi Tri (Universitas Siliwangi, 2024)
Introduction to the Problem: The collaboration potential between Indonesia's halal industry and the K pop entertainment industry offers a strategic opportunity to boost halal product exports. As K pop's popularity grows in Indonesia, this cultural trend could effectively promote Indonesian halal products globally scale. Purpose/Objective Study: This research aims to test and analyze The effect of K-Pop popularity and consumer engagement toward halal product export.Design/Methodology/Approach: This study employs a quantitative approach, utilizing a survey method with 375 respondents, including halal industry stakeholders, marketing experts, and K pop fans in Indonesia. Data were gathered through structured questionnaires measuring perceptions and interests regarding collaboration. The analysis, conducted using descriptive statistics and linear regression, reveals a significant positive correlation between K pop's popularity and consumer interest in halal products endorsed by K pop idols. Findings: Additionally, strategic collaboration with the K pop industry increases consumer purchase intentions for Indonesian halal products, contributing to export growth. These findings suggest that integrating K pop into halal product marketing strategies could effectively expand market reach and enhance the global competitiveness of Indonesia's halal industry.Paper Type: Research Article